A Photographic Essay on Solid Waste Recycling: Street Ethnography and Innovative Experiences in the Netherlands - Cornelia Eckert; Carmen Silvia de Moraes Rial (Vibrant: Virtual Brazilian Anthropology)
Abstract This photographic essay explores solid waste management and recycling practices among residents of Zaandam and other towns in the Netherlands. The study was based on ethnographic research conducted in September 2019 and December 2021 that included street ethnography, landscape observation, and recorded interviews. The photo essay presents a narrative of the researcher’s observations and experiences, highlighting the challenges and successes of waste management and recycling practices in the Netherlands.